City size, technological innovation, and urban income inequality: Empirical evidence from China family panel studies - Zhang, Xinfang; Fu, Yu; Zhuang, Haitao (Frontiers in Environmental Science, 2022)
Using data from the China Family Panel Studies for 2010, 2012, 2014, 2016, and 2018, we establish two fixed-effect model to investigate the roles of city size and technology innovation in urban income inequality, and use a mediating effect model to analyze the impact of city size on urban income inequality via technology innovation. Our findings suggest that urban income inequality tends to increase with city size, technology innovation, and city size will act on urban income inequality through technology innovation. The total sample is divided into three sub-samples: geographical location of city, level of city’s economic development and situation of city’s resource, to discuss the different effects of city size, technology innovation on income inequality. We find that city size has a greater impact on income inequality in western provinces and first-and second-tier cities; similarly, income inequality within non-resource-based cities is more affected by city size. Given the possible endogeneity of city size, we use historical population to construct an instrumental variable (IV). The results of a series of robustness tests support these conclusions.